NGHIÊN CỨU ẢNH HƯỞNG CỦA CÔNG TRÌNH TỚI TRƯỜNG SÓNG, TRƯỜNG DÒNG CHẢY KHU VỰC CỬA TÙNG - QUẢNG TRỊ BẰNG MÔ HÌNH SỐ - Lê, Văn Tuấn; Hoàng, Văn Thành (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH ON THE EFFECT OF THE CONSTRUCTIONS TO THE WAVE, CURRENT FIELD IN CUA TUNG BEACH - QUANG TRI BY MODELFor many years, Cua Tung area has suffered from the effects of rising water and waves, especially during storms. That situation leads to changes in water environment and coastal erosion, directly affecting people's lives and properties; affect the development of tourism, economy - society. The presence of the works here has led to a change in the hydrodynamic regime (waves, currents) and negatively affects the coast and water environment. Confirmed results show that wave height and flow rate are 73.6% and 55.2% according to Nash criteria, at a satisfactory level or higher. Before and after two constructions, the Southern Embankment and the North Embankment of Cua Tung, have shown a clear change in wave regime and flow, causing the waves to be strengthened and causing severe coastal erosion important. The author has proposed a breakwater construction measure off Cua Tung beach, through simulations, it has been shown that the breakwater has a great effect on breaking waves and protecting the coast. Wave height has decreased markedly at the rear of the breakwater. In addition, the barrier dyke also causes the sediment moving from the shore to the sea to be deposited inside the dyke and in the middle of the dyke there is a gap where the offshore sediment enters. The research results contribute to the assessment of the current status of the coastal zone and serve as a basis for ensuring the stability of the water environment, minimizing coastal erosion in order to develop tourism and promote socio-economic development.